Reconstructing Islamic Education Teachers’ Role in Multicultural Learning Practices - Taruddin Taruddin; Ardi Satrial; Syayyid Hussain Nashir; Rilvina Hildayati (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
This study explores the strategic role of Islamic Religious Education teachers in advancing multicultural education within schools and madrasas. Diversity in ethnicity, religion, race, and social class often creates potential tensions, making the presence of Islamic Religious Education teachers essential in cultivating tolerance and harmony. Through a literature review of the National Education Law and the Law on Teachers and Lecturers, combined with thematic analysis of previous research, this study highlights how teachers function as facilitators of multicultural learning. The findings reveal that teachers integrate multicultural values into learning objectives, strengthen Islamic character in instructional materials, apply cooperative learning methods to encourage teamwork, and utilize project-based evaluation to promote inclusivity. Beyond delivering religious content, Islamic Religious Education teachers nurture attitudes of tolerance, inclusivity, and respect for diversity. This research contributes to the development of pedagogical frameworks that empower teachers to implement multicultural education effectively, thereby supporting the creation of a harmonious and religiously grounded society.